Retrospective Analysis of Intervention Medical Rescue Teams Person Over the Age of 65 Years of Age - Timler, Dariusz; Szarpak, Łukasz; Madziała, Marcin (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Introduction Patients 65+ are large group of a emergency medical system (EMS) respond. The aim of the paper was to analyzed the population of patients of EMS from the chosen county. Material and methods Medical documentation of EMS from 2009 from Otwock's County was analyzed. We included only records of patients over 65 years old (n=3046; 44% of total records). The population consist of group of women (n=1858; 61%) and a group of men (n=1188; 39%). Average age of the total group was 78,37+7,71 years old. The group of men was younger than the group of women about 2,5 years. Results The subgroup from the population analyzed between 75-80 years old called EMS the most often. During January 2009 we observed the most of all interventions of EMS (n=349; 11%). During November there was a drop in interventions number (n=206; 7%). Winter time is busy (n=878; 29%) compare to summer time(n=663; 22%). Between 6:00 am and 10:00 pm there are the busiest time. Diseases of the circulatory system and trauma are the main reasons of an emergence call. Conclusions The analysis is a good point to start a conception of functioning EMS for a group of 65+. More investigations have to be done to optimizing EMS.